2018
DOI: 10.1097/scs.0000000000004613
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Calvarial Hemangioma

Abstract: Although a rare entity, it is important to consider congenital calvarial hemangioma in the differential diagnosis of slow growing skull lesions due to the possibility of complications as a result of the hemangioma's intracranial extension, and the potential for treatment. En bloc resection has classically been described as a treatment for such lesions, although our case demonstrates that medical treatment with propranolol therapy may be appropriate in certain situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Large lesions have radiating spicules of bony trabeculae giving it the classical sunray (or sunburst) appearance on CT scans and plain radiography of skull. 3 , 4 , 5 , 51 Sunburst appearance of CHs have been reported by 2 , 3 , 4 , 17 , 18 , 19 , 27 , 28 , 33 , 36 , 39 , 41 , 42 , 44 authors on imaging either in x rays or CT scans. While several authors state that the inner table is usually not violated and that growth occurs by erosion of the outer table, 3 , 5 , 9 there are reports describing not only breech of the inner table of the skull [5] but also the dura 10 , 15 , 16 , 27 , 40 , 51 In 2 of our cases we encountered inner table violation on preoperative CT imaging and in one another on magnetic resonance imaging (MRI) but there was no intradural extension of the tumour in any of our cases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Large lesions have radiating spicules of bony trabeculae giving it the classical sunray (or sunburst) appearance on CT scans and plain radiography of skull. 3 , 4 , 5 , 51 Sunburst appearance of CHs have been reported by 2 , 3 , 4 , 17 , 18 , 19 , 27 , 28 , 33 , 36 , 39 , 41 , 42 , 44 authors on imaging either in x rays or CT scans. While several authors state that the inner table is usually not violated and that growth occurs by erosion of the outer table, 3 , 5 , 9 there are reports describing not only breech of the inner table of the skull [5] but also the dura 10 , 15 , 16 , 27 , 40 , 51 In 2 of our cases we encountered inner table violation on preoperative CT imaging and in one another on magnetic resonance imaging (MRI) but there was no intradural extension of the tumour in any of our cases.…”
Section: Discussionmentioning
confidence: 94%
“…Excluding the papers that deal with radiological approach to diagnosis of calvarial lesions, skull base haemangiomas, other lesions mimicking these like haemangioendothelioma, angiosarcomas, epithelial hyperplasia's, subgaleal haemangiomas, intraosseous venous malformations, aneurysmal bone cysts and those not in the English language we collected a total of 49 reports of 61 cases that are enumerated in Table 2 . 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 The classical radiological appearance of CHs consists of an expansile lytic lesion on computed tomography (CT) scans. 3 , 5 , 13 , 14 , 15 , 17 However, there are reports of finding sclerotic lesions mimicking an osteoma as well and also lesions that expand the diploic space with a central sclerosis resembling osteoblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavernous hemangiomas are more common in the skull, whereas the capillary type is more common in the vertebral column [ 21 , 22 ]. The pathogenesis of calvarial hemangiomas is not yet fully known; however, previous reports suggested that they are congenital [ 23 25 ]. The proliferation and differentiation of the undifferentiated primitive mesenchymal cells, induced by the various stimuli-like traumas, may be the potential etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The cranial CT with a bone window is the diagnostic modality of choice, since it surpasses the sensitivity of simple radiography and allows bone to be defined in a superior way to MRI, giving a detailed image of the cortical and trabecular bone. Although the appearance in the CT can vary, the characteristic image consists of a Brichacek et al (2018) [63] This table shows all the cases published in the literature since 1846, making a difference between locations. The most frequent are the frontal ones, as our case.…”
Section: Discussionmentioning
confidence: 99%